2021
DOI: 10.1002/jemt.23854
|View full text |Cite|
|
Sign up to set email alerts
|

Morphological and elemental evaluation of biochar through analytical techniques and its combined effect along with plant growth promoting rhizobacteria on Vicia faba L. under induced drought stress

Abstract: Drought is a persistent and complex natural vulnerability whose rate and extent of recurrence are expected to increase with climate change. Regardless of the progress made in responding and adapting to water scarcity, drought stress causes severe afflictions.Therefore, the present study has been accomplished in Department of Botany, University of Peshawar to investigate the effect of biochar and plant growth promoting rhizobacteria (PGPR) Cellulomonas pakistanensis (NCCP11) and Sphingobacterium pakistanensis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…et al (2017) who physico-chemically analyzed the apricot and platane wood biochar and suggested that biochar modify the soil pH to alkaline, retain water and several phytonutrients in soil and regulate the electrical conductivity of soil. Similar studies were also performed by other researcher such as Videgain-Marco et al (2020) and suggested that growth of sorghum plants were highly improved by the application of Vitis vinifera L. biochar as organic amendment having remarkable bulk density, improved soil cation exchange capacity and high organic carbon contents which strengthen our present findings.3.2 | Analysis of both strains of PGPRBoth strains of PGPR (NCCP11 & NCCP246) have already been analyzed chemotaxonomically for dominant cellular fatty acids and phylogenetically based on the 16S rRNA gene sequence at National Agricultural Research Center, Islamabad, Pakistan as discussed in our previous article(Nafees et al, 2021). Both PGPR strains conferred their plant growth promoting nature due to the generation capacity of various phytoharmones including indole acetic acid (phosphatase, valine acrylamides, Napthol-As-BI-phosphohydrolase and esterase lipase as analyzed byAhmed et al …”
supporting
confidence: 80%
See 1 more Smart Citation
“…et al (2017) who physico-chemically analyzed the apricot and platane wood biochar and suggested that biochar modify the soil pH to alkaline, retain water and several phytonutrients in soil and regulate the electrical conductivity of soil. Similar studies were also performed by other researcher such as Videgain-Marco et al (2020) and suggested that growth of sorghum plants were highly improved by the application of Vitis vinifera L. biochar as organic amendment having remarkable bulk density, improved soil cation exchange capacity and high organic carbon contents which strengthen our present findings.3.2 | Analysis of both strains of PGPRBoth strains of PGPR (NCCP11 & NCCP246) have already been analyzed chemotaxonomically for dominant cellular fatty acids and phylogenetically based on the 16S rRNA gene sequence at National Agricultural Research Center, Islamabad, Pakistan as discussed in our previous article(Nafees et al, 2021). Both PGPR strains conferred their plant growth promoting nature due to the generation capacity of various phytoharmones including indole acetic acid (phosphatase, valine acrylamides, Napthol-As-BI-phosphohydrolase and esterase lipase as analyzed byAhmed et al …”
supporting
confidence: 80%
“…Both strains of PGPR (NCCP11 & NCCP246) have already been analyzed chemotaxonomically for dominant cellular fatty acids and phylogenetically based on the 16S rRNA gene sequence at National Agricultural Research Center, Islamabad, Pakistan as discussed in our previous article (Nafees et al, 2021). Both PGPR strains conferred their plant growth promoting nature due to the generation capacity of various phytoharmones including indole acetic acid (IAA) and phytoenzymes including acid phosphatase, N‐acetyl‐b‐glucosaminidase, alkaline phosphatase, valine acrylamides, Napthol‐As‐BI‐phosphohydrolase and esterase lipase as analyzed by Ahmed et al (2014).…”
Section: Resultsmentioning
confidence: 99%
“…EC decreased by 9% than PGPR treatment and by 5.6% than biochar treatment Similarly, no. of grains ear −1 , 100-grain weight, grain yield and stover yield increased by 1.9%, 17%, 24.60% and 5.23%, respectively, than PGPR treatment, and by 1.1%,13.44%, 9.5% and 4.38%, respectively, than biochar treatment [ 64 ] Cellulomonas pakistanensis and Sphingobacterium pakistanensis Biochar was produced from wood of Morus alba Pyrolyzed at between 900 and 1100 °C Applications of biochar level were 0 and 5% w/w Pea and bean family ( Vicia faba ) Pot experiment; Drought applied for 13 and 26 days Plants were grown for 26 days PGPR + biochar treatment positively ameliorated fresh and dry weight of leaves by 28.57 and 10.47%, roots 36.36 and 14.28% and shoots by 16 and 10% than sole biochar and PGPR treatments, respectively [ 65 ] Alcaligenes faecalis , and Bacillus amyloliquefaciens ACC deaminase producing Biochar was made from vegetables and fruits Pyrolyzed at 450 °C for 2 h Application of biochar level was: 0.5% Mint ( Mentha piperita L.) Pot experiment: lead stress: 250 mg Pb kg −1 soil Alcaligenes faecalis strain + compost-mixed biochar treatment showed significant results in improving plant chlorophyll content (37%), root dry weight (58%) and nitrogen (46%), phosphorus (39%), and potassium (63%) in leaves of mint than untreated control Lead (artificially induced) uptake also decreased in spinach roots by 43% and potassium uptake increased by 10.5% over untreated control [ 66 ] Pseudomonas aeruginosa , Enterobacter cloacae , Achromobacter xylosoxidans and Leclercia adecarboxylata Drought tolerant and ACC-deaminase producing Biochar was produced from timber waste Pyrolyzed at 389 °C for 80 min. Application of biochar levels were: 0.75 and 1.5% w/w Maize ( Zea mays L.) Drought/moisture conditions: 70% of field capacity (optimum moisture), 50% FC (mild) and 30% FC (severe drought) Duration of plant growth was 3 months (Harvesting at maturity) A. xylosoxidans + 1.5% biochar treatment showed 43% and 25 increase in grain yield pot −1 than A. xylosoxidans and 1.5% biochar using alone A. xylosoxidans + 1.5% biochar showed 19 and 6% higher photosynthetic rate, 30 and 7% hi...…”
Section: Effect Of Co-application Of Biochar and Pgpr On Soil Quality...mentioning
confidence: 99%
“…For instance, combined application of algal biochar (4% w/w) and a PGPR Serratia odorifera to maize, when moisture content was 50% of the field capacity, significantly improved pH by 7 and 5%, EC by 34 and 13%, nitrate by 57 and 34%, phosphorus by 54 and 49%, extractable K by 30 and 15%, and organic matter by 69 and 21% in comparison to biochar alone and PGPR alone treatments, respectively [ 76 ]. Similarly, Nafees et al [ 65 ] co-applied Cellulomonas pakistanensis or Sphingobacterium pakistanensis with biochar to Vicia faba growing on induced drought stress. They found that the combined application increased the water-use efficiency by 43.62%.…”
Section: Co-application Of Biochar and Pgpr Under Environmental Stres...mentioning
confidence: 99%
See 1 more Smart Citation